GREEN BUSINESS IMPLEMENTATION THROUGH THE SUKORAME WASTE MANAGEMENT SYSTEM (SIMPOSKO) - Rhiansyah, Ariadafa Wahyu; Leonard, Natassya Adelia Candradhita; Meilina, Restin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The purpose of this research is to answer the statement problem as follows : What is the current condition of waste management in Sukorame Village and what are the problems that occur in the existing waste management system? How can the concept of green business be applied in waste management in Sukorame Village? And What features does the SIMPOSKO waste management system need to have to support the implementation of green business in waste management in Sukorame Village? This uses a qualitative method with a descriptive approach. This research type is field research. The informants are head of the sukorame sub-district, waste bank administrators, and several community as representatives. The result show that waste management in Sukorame sub-district is still a collection, transport and disposal system without segregation whereas residents are able to produce can produce handicrafts from waste as a green business implementation and this is facilitated by the features in the sukorame waste management system (SIMPOSKO).